(untitled) (International Journal of Engineering and Computer Science, 2017)
Visual Cryptography (VC), a cryptographic technique which allows visual information to be encrypted in such a way that the decryption can be performed by the Human Visual System (HVS), without the help of computers. Visual Cryptography Scheme (VCS) eliminates complex computation problem in decryption process, by stacking operation we can restore the secret image. This property makes VC especially useful for the low computation load requirement. During encryption, the image is encrypted and then it is divided into two shares. Two shares are superimposed to reveal the secret image in the decryption process. The objective of our project is to get the better quality of decrypted image with the same size as the original image. The OR based VCS degrades the contrast by its monotone property. In XOR based scheme, the share images are superimposed with the help of XOR operation which results in perfect reconstruction. Hence, the XOR operation is proposed in decoding process to enhance the contrast, quality, and to reduce noise.